Nickel-based single-crystal hydroxide precursor and positive electrode material, preparation method thereof, positive electrode and battery

CN120622567BActive Publication Date: 2026-11-03YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510830944.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2026-11-03
Estimated Expiration
2045-06-20

AI Technical Summary

Technical Problem

Existing high-nickel ternary cathode materials suffer from poor electrochemical performance and insufficient safety performance due to structural instability and thermodynamic instability, making them difficult to apply on a large scale. Furthermore, traditional preparation methods are complex and do not fully utilize the material's performance.

Method used

Nickel-based single-crystal hydroxide precursors were prepared using a stepwise nucleation-ripening-growth synergistic regulation method. By controlling the reaction conditions and feeding method, a single-crystal precursor with regular morphology, micro-nano scale, and high dispersion was obtained, avoiding high-temperature high-lithium-ratio sintering, and preparing cathode materials with few or no defects in lithium storage structure.

Benefits of technology

A highly dispersed, regularly morphologically regular single-crystal cathode material has been developed, exhibiting high specific capacity, good rate performance, and excellent reversibility. This simplifies the preparation process, reduces energy consumption, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622567B_ABST
    Figure CN120622567B_ABST
Patent Text Reader

Abstract

The application relates to the field of battery materials, and discloses a nickel-based single-crystal hydroxide precursor and a positive electrode material, a preparation method of the positive electrode material, a positive electrode and a battery. The disclosed precursor is a primary particle, the D50 of the primary particle is 1-5 microns, the specific surface area is <10 m 2 / g. The preparation method comprises the following steps: passing a mixed metal salt solution, an alkali solution and ammonia water into a reaction kettle in parallel, controlling the pH of the reaction kettle to be 12.5-13.0, maintaining the ammonia concentration to be 1.5-2.5 mol / L, and keeping for 20-60 min; stopping the feeding, and keeping for 20-60 min; circulating the above process for 3-10 times; stopping the feeding of the mixed metal salt solution, adjusting the pH to be 10.5-11.5, adjusting the ammonia concentration to be 1.5-2.5 mol / L, and stopping all the feeding after the target particle size is reached. The precursor is a true single-crystal material, has a regular morphology, a preferable size and a preferable dispersity, and the positive electrode material prepared from the precursor has preferable electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to nickel-based single-crystal hydroxide precursors and cathode materials, their preparation methods, cathodes, and batteries. Background Technology

[0002] High-nickel ternary cathode materials, as an important component of lithium-ion batteries, have attracted much attention due to their unique advantages in energy density and cycle stability. However, the large-scale application of high-nickel (Ni≥80%) ternary cathode materials, especially ultra-high-nickel (Ni>90%) cathode materials, is severely restricted by their poor electrochemical performance and insufficient safety performance caused by structural instability and thermodynamic instability. Large-particle polycrystalline spherical structures and single-crystal structures are the two most common particle structures for high-nickel cathode materials. Among them, large-particle polycrystalline spherical particles are formed by the agglomeration of anisotropic primary nanocrystalline single-crystal particles, with a size of about 3-20 μm, exhibiting good fluidity and low specific surface area. However, secondary particles agglomerated by intermolecular forces are prone to breakage during electrode rolling. In addition, the disordered volume effect of anisotropic primary particles during charge-discharge cycles leads to the generation and propagation of intergranular and lattice cracks, exacerbating the side reactions at the material surface and interface, and causing a sharp decline in the volumetric energy density, structural stability, and thermal stability of large-particle polycrystalline layered nickel-based oxide cathode materials. This is also a major problem currently facing commercialized polycrystalline and agglomerated cathode materials.

[0003] Single-crystal particle structures can improve the structural stability of materials, effectively solving the aforementioned problems of polycrystalline materials. The particle structure of nickel-based hydroxide precursors directly affects the sintering process of single-crystal high-nickel cathode materials. In its previous research on the synthesis of single-crystal NCA cathode materials, the applicant discovered that Ni… 0.8 Co 0.15 Al 0.05 The particle size and specific surface area of ​​the (OH)₂ precursor determine the size and electrochemical performance of the single-crystal finished material. Small particle size (3–5 μm) and high specific surface area (~40 μm²) are desirable. 2 Due to its high reactivity, the precursor (e.g., 1 / g) can be used to prepare monodisperse single-crystal NCA cathode materials at a sintering temperature of 800℃ and a lithium ratio of 1.15. Its volumetric energy density and electrochemical stability are far superior to those of large-particle polycrystalline spherical structures [Journal of Alloys and Compounds, 2017, 695: 9199]. However, even with this small-particle-size, high-specific-surface-area precursor, high-temperature, high-over-lithium-ratio sintering is still unavoidable when constructing single-crystal high-nickel cathode materials. The reversibility, rate performance, and cycle performance of the obtained single-crystal cathode materials remain insufficient.

[0004] To address these issues, the preparation method for large-particle single-crystal lithium-ion battery ternary cathode materials disclosed in CN109286016A in 2018 uses a polycrystalline precursor, requiring wet mixing and drying before sintering, and sintering in a rotary furnace, making the process complex. Furthermore, the single-crystal ternary materials prepared using this method have irregular particle morphology and excessively large sizes, which is detrimental to the material's performance. The preparation method for high-nickel ternary single-crystal material precursors disclosed in CN114436346A in 2022 obtains single-crystal precursor materials by co-precipitating inorganic and organic dispersants. However, this process requires the addition of additional dispersants and the washing of impurities with ethanol solution, and the resulting single-crystal precursor materials are prone to agglomeration. In 2022, Kunming University of Science and Technology disclosed a method (CN115028210B) for preparing single-crystal high-nickel cathode materials. This method uses an ammonia complexation-boiling precipitation method to prepare single-crystal doped nickel hydroxide precursors with relatively large primary particles. This avoids the harsh conditions such as high temperature and high lithium over-ratio, as well as the complicated processes such as water washing involved in the preparation of traditional single-crystal cathode materials. However, the precursor obtained by this method is a spherical / quasi-spherical aggregate of large sheet-like primary particles. The resulting single-crystal cathode material still needs to be crushed and graded. Furthermore, the reaction rate is too fast under boiling conditions to achieve controllable preparation, making the operation difficult and the volatilization of ammonia hard to control. Therefore, in order to achieve performance improvement and large-scale application of ultra-high specific capacity and high rate nickel-based layered oxide cathode materials, it is urgent to develop highly dispersed single-crystal precursors and their controllable preparation technology.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide nickel-based single-crystal hydroxide precursors and cathode materials, methods for their preparation, cathodes, and batteries, aiming to improve at least one of the problems mentioned in the background art.

[0007] This invention is implemented as follows:

[0008] In a first aspect, the present invention provides a nickel-based single-crystal hydroxide precursor, the chemical formula of which is Ni 1-x-y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3;

[0009] The precursor is a primary particle with a D50 of 1–5 μm, a single crystal primary particle size range of 0.2–2 μm, and a polyhedral morphology.

[0010] In an optional embodiment, the polyhedron is a prism-shaped cubic polyhedron with a lateral aspect ratio of (1-5):1 and a specific surface area of ​​<10m². 2 / g.

[0011] Secondly, embodiments of the present invention provide a method for preparing the aforementioned precursor, comprising:

[0012] Stepwise nucleation:

[0013] Nucleation: A mixed metal salt solution, an alkaline solution, and ammonia water are introduced into the reaction vessel in a parallel flow. The pH of the reaction vessel is controlled at 12.5–13.0, and the ammonia concentration is maintained at 1.5–2.5 mol / L for 20–60 min.

[0014] Maturation: Stop feeding the mixed metal salt solution, alkaline solution and ammonia water, and maintain for 20-60 minutes;

[0015] The cyclic nucleation-ripening step is repeated 3 to 10 times to complete the hierarchical nucleation;

[0016] Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia water to make the solution pH 10.5-11.5, maintain the ammonia concentration 1.5-2.5 mol / L, and stop all feeding after 20-100 h to reach the target particle size;

[0017] The slurry is aged for 0.5–2 hours;

[0018] The entire reaction process takes place at a temperature of 60–90°C.

[0019] In an optional embodiment, the preparation method includes at least one of the following features (1) to (4):

[0020] (1) The bottom liquid in the reactor accounts for 50-60% of the reactor volume, the ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0;

[0021] (2) The concentration of metal ions in the mixed metal salt solution is 1 to 2 mol / L, and the injection flow rate of the mixed metal salt solution during nucleation is 10 mL / min to 2 L / min;

[0022] (3) After aging, the following steps are taken: the precipitate is extracted from the slurry, and washed sequentially with alkaline solution and deionized water at a temperature of 60-90℃ until the pH value of the precipitate is below 10, and then dried to obtain the precursor.

[0023] (4) The concentration of the ammonia water is 10-14 mol / L; the alkaline solution is sodium hydroxide solution with a concentration of 8-10 mol / L.

[0024] In an optional embodiment, the flow rate of ammonia water is 5 mL / min to 1 L / min, and the flow rate of sodium hydroxide solution is 5 mL / min to 1 L / min.

[0025] Thirdly, embodiments of the present invention provide a method for preparing a cathode material, comprising mixing and sintering a lithium source and the aforementioned precursor, wherein the molar ratio of lithium in the lithium source to the metal in the precursor is 1:1.01 to 1.05.

[0026] In an optional embodiment, the sintering conditions are: holding at 400-500°C for 2-6 hours in an oxygen atmosphere, then raising the temperature to 680-750°C and holding for 8-15 hours.

[0027] Fourthly, the present invention provides a positive electrode material, which is prepared by the preparation method described in the foregoing embodiments.

[0028] Fifthly, the present invention provides a positive electrode, comprising a positive electrode material as described in the foregoing embodiments or a positive electrode material prepared by the preparation method described in the foregoing embodiments.

[0029] In a sixth aspect, the present invention provides a battery comprising a positive electrode as described in the foregoing embodiments.

[0030] The present invention has the following beneficial effects:

[0031] The nickel-based single-crystal hydroxide precursor provided by this invention is a true single-crystal material with a regular morphology, good size, and good dispersibility. When used to prepare cathode materials, it can be sintered without crushing or grading. The cathode materials obtained can inherit the crystal structure of the single-crystal precursor and have lithium storage structure characteristics with few or no defects. It has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0032] The preparation method provided by this invention develops a novel single-crystal precursor preparation technology with synergistic regulation of nucleation, ripening, and growth. By using a step-feed nucleation technology, the agglomeration of amorphous nanocrystal nuclei is greatly reduced, and micro-nano-scale, highly dispersed, and pre-ripened nickel-based single-crystal hydroxide nuclei are prepared. The crystal growth is synergistically controlled, and highly dispersed, large single-crystal hydroxide precursors can be controllably prepared. Attached Figure Description

[0033] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0034] Figures 1 to 5 The images shown are SEM images of the precursors obtained in Examples 1 to 5, respectively.

[0035] Figures 6 to 10 The XRD patterns of the precursors prepared in Examples 6 to 10 are shown in turn.

[0036] Figure 11 This is a SEM image of the cathode material prepared in Example 3. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0038] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0039] This invention provides a nickel-based single-crystal hydroxide precursor, the precursor having the chemical formula Ni. 1-x- y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3;

[0040] The precursor is a primary particle with a D50 of 1–5 μm. The single-crystal primary particle size ranges from 0.2 to 2 μm and has a polyhedral morphology.

[0041] The nickel-based single-crystal hydroxide precursor provided in this embodiment of the invention is a true single-crystal material with a regular morphology, good size, and good dispersibility. When used to prepare cathode materials, it does not require crushing or grading after sintering. The cathode materials obtained can inherit the crystal structure of the single-crystal precursor and have lithium storage structure characteristics with few or no defects. It has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0042] Optionally, the precursor has a polyhedral structure that is a prism-shaped cubic polyhedron with a lateral aspect ratio of (1-5):1 and a specific surface area of ​​<10m². 2 / g.

[0043] The method for preparing the precursor provided in this embodiment of the invention includes:

[0044] Stepwise nucleation:

[0045] Nucleation: A mixed metal salt solution, an alkaline solution, and ammonia water are introduced into the reaction vessel in a parallel flow. The pH of the reaction vessel is controlled at 12.5–13.0, and the ammonia concentration is maintained at 1.5–2.5 mol / L for 20–60 min.

[0046] Maturation: Stop feeding the mixed metal salt solution, alkaline solution and ammonia water, and maintain for 20-60 minutes;

[0047] The cyclic nucleation-ripening step is repeated 3 to 10 times to complete the hierarchical nucleation;

[0048] Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia water to make the solution pH 10.5-11.5, maintain the ammonia concentration 1.5-2.5 mol / L, and stop all feeding after 20-100 h to reach the target particle size;

[0049] The slurry is aged for 0.5–2 hours;

[0050] The entire reaction process takes place at a temperature of 60–90°C.

[0051] The preparation method provided by this invention develops a novel single-crystal precursor preparation technology with synergistic regulation of nucleation, ripening, and growth. By employing a step-feed nucleation technique, the agglomeration of amorphous nanocrystalline nuclei is significantly reduced, resulting in the preparation of micro / nano-scale, highly dispersed, and pre-ripened nickel-based single-crystal hydroxide nuclei. Synergistic control of crystal growth enables the controllable preparation of highly dispersed, large single-crystal hydroxide precursors. The single-crystal precursor prepared by this method exhibits a controllable primary particle D50 of 1–5 μm, uniform particle size distribution, high dispersion, and controllable crystal structure. The process is simple and requires no additional dispersant. This single-crystal precursor has a uniform morphology, good product consistency, and can be mass-produced. Its application to the synthesis of single-crystal cathode materials avoids the drawbacks of traditional methods, such as high lithium overload and high-temperature calcination, thus saving energy and reducing consumption from the source, promoting a green and economical approach. The cathode material obtained from this precursor inherits the crystal structure characteristics of the single-crystal precursor, possessing a low-defect or defect-free lithium storage structure, and exhibits advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0052] Specifically, the preparation method is as follows:

[0053] S1. Prepare the base liquid

[0054] Deionized water, ammonia water, and sodium hydroxide solution are introduced into the reactor so that the bottom liquid in the reactor occupies 50-60% of the reactor volume. The ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0.

[0055] S2, hierarchical nucleation

[0056] Nucleation: The temperature inside the reactor is controlled at 60-90℃. An inert gas (such as nitrogen or argon) is introduced into the reactor. Then, a mixed metal salt solution, ammonia water and alkaline solution are introduced into the reactor in parallel. Throughout the process, the pH of the reactor is controlled at 12.5-13.0, the ammonia concentration is maintained at 1.5-2.5 mol / L, and the process is maintained for 20-60 min.

[0057] Cook until tender, then stop feeding and maintain for 20–60 minutes;

[0058] Repeat the nucleation-ripening step 3 to 10 times.

[0059] In this step, micro- and nano-scale, highly dispersed, and pre-ripened nickel-based single-crystal hydroxide nuclei are prepared under high pH conditions. Then, the pH is lowered to the nucleus growth point, allowing the single-crystal nuclei to grow slowly. The nucleation-ripening steps are repeated to obtain micron-scale nickel-based single-crystal hydroxide precursors.

[0060] Optionally, the mixed metal salt solution contains nickel ions, and may contain manganese ions and cobalt ions; the types and proportions of metal ions included depend on the chemical formula of the precursor to be prepared.

[0061] Optionally, the salt used to prepare the mixed metal salt solution can be a salt that is currently known to be used to prepare the precursor, such as a sulfate, specifically, for example, NiSO4·6H2O, CoSO4·7H2O, or MnSO4·H2O.

[0062] Optionally, the concentration of metal ions in the mixed metal salt solution is 1–2 mol / L, and the injection flow rate of the mixed metal salt solution during nucleation is 10 mL / min–2 L / min;

[0063] Optionally, the concentration of ammonia water is 10–14 mol / L, and the flow rate of ammonia water is dynamically controlled within the range of 5 mL / min to 1 L / min throughout the process to ensure that the ammonia value and pH value are within the required range; the alkaline solution is sodium hydroxide solution with a concentration of 8–10 mol / L, and the flow rate of sodium hydroxide solution is dynamically controlled within the range of 5 mL / min to 1 L / min throughout the process to ensure that the pH value is within the required range.

[0064] Optionally, the nucleation and ripening processes are carried out under continuous stirring at a speed of 500–900 rpm.

[0065] S3, growth

[0066] Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia water to make the solution pH 10.5-11.5 and maintain the ammonia concentration 1.5-2.5 mol / L. After maintaining this for 20-100 hours until the target particle size is reached, stop all feeding.

[0067] Optionally, the growth stage is carried out under continuous stirring at a speed of 500–900 rpm.

[0068] During the growth stage, lowering the pH value promotes rapid growth of grains along the dominant crystal plane, enabling the grains to grow to the target size.

[0069] S4, Aging

[0070] After the growth stage is completed, allow the slurry to age for 0.5 to 2 hours to allow the solution system to stabilize and the transition metals to precipitate fully.

[0071] S5. Extract the precursor.

[0072] The aged slurry was filtered, and then the filter material was washed sequentially with a 5% sodium hydroxide solution at a temperature of 60-90℃ and deionized water until the pH value of the filtrate after washing was lower than 10, indicating that the washing was complete. After solid-liquid separation, the slurry was placed in a forced-air drying oven at 100-150℃ and dried for 10-20 hours to obtain a true single crystal high-nickel-based precursor with good particle size, good morphology, and good dispersion uniformity.

[0073] The present invention provides a cathode material with the chemical formula LiNi. 1-x-y Co x Mn y O2, where 0 ≤ x ≤ 0.2, 0 ≤ y ≤ 0.2;

[0074] The precursor consists of primary particles with a D50 of 1–5 μm, and single-crystal primary particle size ranging from 0.2–2 μm. The morphology is polyhedral, specifically a prismatic cubic polyhedron with a lateral aspect ratio of (1–5):1 and a specific surface area <10 m². 2 / g.

[0075] This cathode material is a true single crystal material with better size, better dispersion, and lithium storage structure characteristics with few or no defects. It has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0076] The present invention provides a method for preparing a cathode material, comprising mixing and sintering a lithium source with a precursor provided in the present invention, wherein the molar ratio of lithium in the lithium source to metal in the precursor is 1:1.01 to 1.05.

[0077] Optionally, the lithium source is at least one of lithium carbonate and lithium hydroxide.

[0078] Specifically, the sintering conditions are: holding at 400–500°C for 2–6 hours in an oxygen atmosphere, then raising the temperature to 680–750°C and holding for 8–15 hours.

[0079] Because the precursor prepared using the embodiments of this invention is used to prepare the cathode material, the sintering temperature is low (less than 800°C), which avoids crystal defects caused by recrystallization. The obtained true single-crystal high-nickel cathode material perfectly inherits the crystal structure of the single-crystal precursor, has the characteristics of lithium storage structure with few or no defects, and has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0080] The positive electrode provided in the embodiments of the present invention includes the positive electrode material provided by the present invention.

[0081] The battery provided in this embodiment of the invention includes a positive electrode provided in this embodiment of the invention.

[0082] Example 1

[0083] This embodiment provides a nickel-based single-crystal hydroxide precursor, a single-crystal cathode material, and a method for preparing the same.

[0084] The chemical formula of the nickel-based single-crystal hydroxide precursor is LiNi 0.89 Co 0.07 Mn 0.04 (OH)2;

[0085] The molecular formula of the single-crystal cathode material is LiNi. 0.89 Co 0.07 Mn 0.04 O2;

[0086] The specific preparation method of the precursor is as follows:

[0087] Step 1: Mix NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in the order n(Ni 2+ ): n(Co 2+ ): n(Mn 2+ Mix the metal salts in a ratio of 89:7:4 evenly to prepare a 2 mol / L mixed solution; prepare a 10 mol / L sodium hydroxide solution; and prepare a 10 mol / L ammonia solution.

[0088] In a 100L reactor, 45L of deionized water and 11L of ammonia water were pre-added as a base solution. An appropriate amount of sodium hydroxide solution was added to control the pH of the base solution to 12.5 (±0.05). The ammonia concentration in the base solution was 2 mol / L. After completely sealing the reaction vessel and testing its airtightness, nitrogen gas (0.2m³) was introduced. 3The protective gas is used to completely replace the oxygen in the reactor. When the temperature inside the reactor reaches 80℃, the metal salt mixture, sodium hydroxide solution, and ammonia water are pumped into the reactor at flow rates of 40mL / min, 16mL / min, and 16mL / min, respectively, while the stirring speed is controlled at 800r / min. By adjusting the flow rates of sodium hydroxide solution and ammonia, the pH of the entire reactor was maintained at 12.5 (±0.05), and the ammonia concentration at 2 (±0.05) mol / L. Nucleation was carried out in stages for 8 hours (with four cycles, each lasting 60 minutes for nucleation and 60 minutes for maturation). After the reaction was complete, the flow rate of the alkaline solution was reduced, causing the pH of the solution in the reactor to slowly decrease to 10.50 (±0.05), while maintaining the ammonia concentration. The reaction continued for 20 hours, after which all feeding was stopped. The slurry was aged for 30 minutes, the mother liquor was filtered, and washed with 60℃ alkaline solution (5% sodium hydroxide solution) for 30 minutes, followed by washing with 60℃ deionized water until the pH was below 10. Then, it was filtered again and placed in a 100℃ forced-air drying oven for 20 hours to obtain Ni. 0.89 Co 0.07 Mn 0.04 (OH)2 precursor sample, SEM image is shown below. Figure 1 The D50 is 3.8 μm, the primary grain size of single crystals ranges from 0.3 to 1.0 μm, the single crystal morphology is polyhedral, and the single crystal is a prismatic cubic polyhedron with a lateral aspect ratio of (1–5):1 and a specific surface area of ​​3.4 m². 2 / g.

[0089] The preparation method of the positive electrode material is as follows:

[0090] Step 2: The precursor prepared in Step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 and thoroughly ball-mixed for 60 min to ensure homogeneity. The mixture was then placed in a tube furnace for high-temperature sintering under oxygen-rich conditions. The heating rate was controlled at 3℃ / min; the temperature was raised to 450℃ and held for 3 h, then further raised to 750℃ and held for 12 h. After natural cooling to room temperature, the sample was removed and ground to obtain the single-crystal cathode material LiNi. 0.89 Co 0.07 Mn 0.04 O2.

[0091] Currently, the sintering temperature for single-crystal cathode materials with a nickel-cobalt-manganese ratio of 0.89:0.07:0.04 is typically 800℃. In this embodiment, the calcination temperature is 750℃, which is 50℃ lower than the existing technology, thus saving energy.

[0092] Example 2

[0093] This embodiment provides a nickel-based single-crystal hydroxide precursor, a single-crystal cathode material, and a method for preparing the same.

[0094] The chemical formula of the nickel-based single-crystal hydroxide precursor is LiNi 0.92 Co 0.05 Mn 0.03 (OH)2;

[0095] The molecular formula of the single-crystal cathode material is LiNi. 0.92 Co 0.05 Mn 0.03 O2;

[0096] The specific preparation method of the precursor is as follows:

[0097] Step 1: Mix NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in the order n(Ni 2+ ): n(Co 2+ ): n(Mn 2+ Mix the metal salts in a ratio of 92:5:3 until homogeneous to prepare a 1.5 mol / L mixed solution; prepare a 10 mol / L sodium hydroxide solution; and prepare a 14 mol / L ammonia solution.

[0098] 50L of deionized water and 6L of ammonia solution were pre-added to a 100L reactor as a base solution. The pH of the base solution was controlled to 12.7 (±0.05) with sodium hydroxide solution, and the ammonia concentration was 1.5 mol / L. After completely sealing the reaction vessel and testing its airtightness, nitrogen gas (0.2m³) was introduced. 3 / h), to completely replace the oxygen in the reactor with protective gas. When the temperature inside the reactor reaches 70℃, the mixed metal salt solution, sodium hydroxide solution, and ammonia water are pumped into the reactor at flow rates of 80 mL / min, 24 mL / min, and 20 mL / min, respectively. The stirring speed is controlled at 800 r / min. By adjusting the flow rates of sodium hydroxide solution and ammonia water, the pH value of the entire reactor is maintained at 12.7 (±0.05), and the ammonia concentration is maintained at 1.5 (±0.05) mol / L. Nucleation is carried out in stages for 5 hours (with a total of 5 cycles, each for 30 minutes of nucleation and 30 minutes of maturation). After the reaction is completed, the flow rate of the alkaline solution is reduced, so that the pH of the solution in the reactor slowly decreases to 11.30 (±0.05), and the reaction continues for 80 hours. After the reaction is completed, the slurry is aged for 1 hour, and then washed, filtered, and dried using the same method as in Example 1 above. LiNi is obtained. 0.92 Co 0.05 Mn 0.03 (OH)2 precursor sample, SEM image is shown below. Figure 2 The D50 is 2.8 μm, the primary grain size of single crystals ranges from 0.2 to 0.8 μm, the single crystal morphology is polyhedral, and the single crystal is a prismatic cubic polyhedron with a lateral aspect ratio of (1–5):1 and a specific surface area of ​​5.6 m². 2 / g.

[0099] Step 2: The precursor prepared in Step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.03 and thoroughly ball-mixed for 60 min to ensure homogeneity. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-enriched conditions. The heating rate was controlled at 3℃ / min; the temperature was raised to 480℃ and held for 4 h, then further raised to 720℃ and held for 12 h. After natural cooling to room temperature, the sample was removed and ground to obtain the single-crystal cathode material LiNi. 0.92 Co 0.05 Mn 0.03 O2.

[0100] Currently, the sintering temperature for single-crystal cathode materials with a nickel-cobalt-manganese ratio of 0.92:0.05:0.03 is typically 780℃. In this embodiment, the calcination temperature is 720℃, which is 60℃ lower than the existing technology, thus saving energy.

[0101] Example 3

[0102] This embodiment provides a nickel-based single-crystal hydroxide precursor, a single-crystal cathode material, and a method for preparing the same.

[0103] The chemical formula of the nickel-based single-crystal hydroxide precursor is LiNi 0.92 Co 0.05 Mn 0.03 (OH)2;

[0104] The molecular formula of the single-crystal cathode material is LiNi. 0.92 Co 0.05 Mn 0.03 O2;

[0105] The specific preparation method of the precursor is as follows:

[0106] Step 1: Prepare the same metal salt mixture, sodium hydroxide solution, and ammonia solution as in Example 2. In a 100L reactor, pre-add 45L of deionized water and 10L of ammonia solution as the base solution. Control the pH of the base solution to 12.5 (±0.05) with sodium hydroxide solution, and maintain the ammonia concentration at 2.5 mol / L. After completely sealing the reaction vessel and testing its airtightness, begin introducing nitrogen gas (0.2m³ / L). 3 / h), ensuring the protective gas completely replaces the oxygen in the reactor. When the temperature inside the reactor reaches 80℃, the metal salt mixture, sodium hydroxide solution, and ammonia water are pumped into the reactor at flow rates of 80mL / min, 24mL / min, and 24mL / min, respectively. The stirring speed is controlled at 700r / min. By adjusting the flow rates of the sodium hydroxide solution and ammonia water, the pH value of the entire reactor is maintained at 12.5 (±0.05), and the ammonia concentration is maintained at 2.5 (±0.05) mol / L. Nucleation is carried out in stages for 3 hours (with a total of 3 cycles, each for 30 minutes of nucleation and 30 minutes of maturation). After the reaction is completed, the alkaline feed is stopped, and the pH of the solution in the reactor is reduced to 10.8 (±0.05). The reaction continues for 100 hours. After the reaction is completed, the slurry is aged for 1 hour and then washed, filtered, and dried using the same method as in Example 1 above. LiNi is obtained. 0.92 Co 0.05 Mn 0.03 (OH)2 precursor samples, such as Figure 3 As shown, the D50 is 4.2 μm, the primary grain size of the single crystal ranges from 0.6 to 2.0 μm, the single crystal morphology is polyhedral, and the single crystal is a prismatic cubic polyhedron with an aspect ratio of (1–5):1 on the prism's lateral facets, and the specific surface area is 2.9 m². 2 / g.

[0107] Step 2: The precursor prepared in Step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 and thoroughly ball-mixed for 60 min to ensure homogeneity. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-enriched conditions. The heating rate was controlled at 3℃ / min; the temperature was raised to 450℃ and held for 4 h, then further raised to 720℃ and held for 12 h. After natural cooling to room temperature, the sample was removed and ground to obtain the single-crystal cathode material LiNi. 0.92 Co 0.05 Mn 0.03 O2.

[0108] Currently, the sintering temperature for single-crystal cathode materials with a nickel-cobalt-manganese ratio of 0.92:0.05:0.03 is typically 780℃. In this embodiment, the calcination temperature is 720℃, which is 60℃ lower than the existing technology, thus saving energy.

[0109] Example 4

[0110] This embodiment provides a nickel-based single-crystal hydroxide precursor, a single-crystal cathode material, and a method for preparing the same.

[0111] The chemical formula of the nickel-based single-crystal hydroxide precursor is LiNi 0.94 Co 0.05 Mn 0.01 (OH)2;

[0112] The molecular formula of the single-crystal cathode material is LiNi. 0.94 Co 0.05 Mn 0.01 O2;

[0113] The specific preparation method of the precursor is as follows:

[0114] Step 1: Mix NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in the order n(Ni 2+ ): n(Co 2+ ): n(Mn 2+ Mix the metal salts in a ratio of 94:5:1 until homogeneous to prepare a 2 mol / L mixed solution; prepare a 10 mol / L sodium hydroxide solution; and prepare a 14 mol / L ammonia solution.

[0115] 50L of deionized water and 8L of ammonia solution were pre-added to a 100L reactor as a base solution. The pH of the base solution was controlled to be 12.6 (±0.10) with sodium hydroxide solution, and the ammonia concentration was 2.0 mol / L. After the reaction was completely sealed and its airtightness was checked, nitrogen gas (0.2 m³ / L) was introduced. 3 / h), so that the protective gas completely replaces the oxygen in the reactor. When the temperature inside the reactor reaches 70℃, the metal salt mixed solution, sodium hydroxide solution, and ammonia water are pumped into the reactor at flow rates of 80mL / min, 32mL / min, and 32mL / min, respectively. The stirring speed is controlled at 600r / min. By adjusting the flow rates of sodium hydroxide solution and ammonia water, the pH value of the entire reactor is maintained at 12.6 (±0.05), and the ammonia concentration is maintained at 2.0 (±0.05) mol / L. Nucleation is carried out in stages for 5 hours (with a total of 6 cycles, each for 25 minutes of nucleation and 25 minutes of maturation). After the reaction is completed, the alkaline solution feed is stopped, and the pH of the solution in the reactor is reduced to 11.1 (±0.05). The reaction is continued for 80 hours. After the reaction is completed, the slurry is aged for 2 hours and then washed, filtered, and dried using the same method as in Example 1 above. Ni is obtained. 0.94 Co 0.05 Mn 0.01 (OH)2 precursor samples, such as Figure 4 As shown, the D50 is 5.0 μm, the primary grain size of the single crystal ranges from 1.0 to 2.0 μm, the single crystal morphology is polyhedral, and the single crystal is a prismatic cubic polyhedron with a lateral aspect ratio of (1–5):1 and a specific surface area of ​​4.7 m². 2 / g.

[0116] Step 2: The precursor prepared in Step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.03 and thoroughly ball-mixed for 60 min to ensure homogeneity. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-enriched conditions. The heating rate was controlled at 3℃ / min; the temperature was raised to 450℃ and held for 4 h, then further raised to 700℃ and held for 12 h; finally, it was allowed to cool naturally to room temperature. The sample was then removed and ground to obtain the single-crystal cathode material LiNi. 0.94 Co 0.05 Mn 0.01 O2.

[0117] Currently, the sintering temperature for single-crystal cathode materials with a nickel-cobalt-manganese ratio of 0.94:0.05:0.01 is typically 760℃. In this embodiment, the calcination temperature is 700℃, which is 60℃ lower than the existing technology, thus saving energy.

[0118] Example 5

[0119] This embodiment provides a nickel-based single-crystal hydroxide precursor, a single-crystal cathode material, and a method for preparing the same.

[0120] The chemical formula of the nickel-based single-crystal hydroxide precursor is LiNi 0.94 Co 0.05 Mn 0.01 (OH)2;

[0121] The molecular formula of the single-crystal cathode material is LiNi. 0.94 Co 0.05 Mn 0.01 O2;

[0122] The specific preparation method of the precursor is as follows:

[0123] Step 1: Prepare the same metal salt mixture, sodium hydroxide solution, and ammonia solution as in Example 4. In a 100L reactor, pre-add 50L of deionized water and 8L of ammonia solution as the base solution. Control the pH of the base solution to 12.70 (±0.10) with sodium hydroxide solution, and the ammonia concentration to 2 mol / L. After completely sealing the reaction vessel and testing its airtightness, begin purging with nitrogen gas (0.2 m³ / h) to completely replace the oxygen in the reactor with the protective gas. When the temperature inside the reactor reaches 90°C... A mixed solution of metal salts, sodium hydroxide solution, and ammonia were pumped into the reactor at flow rates of 80 mL / min, 32 mL / min, and 32 mL / min, respectively. The stirring speed was controlled at 800 r / min. The pH value of the entire reactor was maintained at 12.7 (±0.05) and the ammonia concentration was maintained at 2.0 (±0.05) mol / L by adjusting the flow rates of the sodium hydroxide solution and ammonia. Nucleation was carried out in stages for 2 hours (with a total of 3 cycles, each for 20 minutes of nucleation and 20 minutes of maturation). After the reaction was completed, the alkaline solution feed was stopped, and the pH of the solution in the reactor was lowered to 10.80 (±0.05). The reaction was continued for 80 hours. After the reaction was completed, the slurry was aged for 2 hours and then washed, filtered, and dried using the same method as in Example 1 above. LiNi was thus obtained. 0.94 Co 0.05 Mn 0.01 (OH)2 precursor samples, such as Figure 5 As shown, the D50 is 4.9 μm, the primary grain size of the single crystal ranges from 1.2 to 1.8 μm, the single crystal morphology is polyhedral, and the single crystal is a prismatic cubic polyhedron with an aspect ratio of (1–5):1 on the prism's lateral facets, and the specific surface area is 2.3 m². 2 / g.

[0124] Step 2: The precursor prepared in Step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 and thoroughly ball-mixed for 60 min to ensure homogeneity. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-enriched conditions. The heating rate was controlled at 3℃ / min; the temperature was raised to 450℃ and held for 4 h, then further raised to 680℃ and held for 12 h. After natural cooling to room temperature, the sample was removed and ground to obtain the single-crystal cathode material LiNi. 0.94 Co 0.05 Mn 0.01 O2.

[0125] Currently, the sintering temperature for single-crystal cathode materials with a nickel-cobalt-manganese ratio of 0.94:0.05:0.01 is typically 760℃. In this embodiment, the calcination temperature is 680℃, which is 80℃ lower than the existing technology, thus saving energy.

[0126] Comparative Example 1

[0127] This comparative example is basically the same as Example 1, except that: in the preparation of the precursor, the ripening process in the staged nucleation process is cancelled, the mixed metal salt solution is directly injected, and the pH is controlled at 12.5 (±0.05) and the ammonia concentration is maintained at 2 (±0.05) mol / L, and the reaction is carried out for 8 hours.

[0128] Comparative Example 2

[0129] This comparative example is basically the same as Example 1, except that: in the staged nucleation step, nucleation is performed continuously for 4 hours, followed by 4 hours of ripening, without any cycling.

[0130] Comparative Example 3

[0131] This comparative example is basically the same as Example 1, except that in the staged nucleation step, the pH value of the nucleation process is controlled at 12 (±0.05).

[0132] Comparative Example 4

[0133] This comparative example is basically the same as Example 1, except that the n(Ni) content in the prepared precursor and cathode material is different. 2+ ): n(Co 2+ ): n(Mn 2+ = 6:3:1.

[0134] Comparative Example 5

[0135] This comparative example is basically the same as Example 4, except that the preparation method is the conventional precursor preparation method. Specifically, in the precursor preparation process, the ripening process in the staged nucleation process is eliminated, and the mixed metal salt solution is directly injected, and the pH is controlled at 12.5 (±0.05) and the ammonia concentration is maintained at 2 (±0.05) mol / L, and the reaction is carried out for 8 hours.

[0136] Experimental Example 1

[0137] SEM images of the precursors for each embodiment were prepared. The SEM images of embodiments 1 to 5 are as follows: Figures 1 to 5 ,from Figures 1 to 5 It can be seen that the precursors obtained in each embodiment are uniformly dispersed primary particles, and the particles are polyhedral in shape.

[0138] XRD patterns of the cathode materials prepared in each embodiment were generated. The XRD patterns of the cathode materials prepared in Examples 1 to 5 are as follows: Figures 6 to 10 ,from Figures 6 to 10 As can be seen, the cathode material prepared in the example has a typical αNaFeO3 layered structure XRD pattern with no other impurity peaks, indicating that the obtained material is a single pure phase.

[0139] SEM images were prepared using the cathode material obtained in Example 3 as an example, such as... Figure 11 As shown, from Figure 11 It can be seen that the prepared cathode material has no agglomeration, uniform particle size distribution, and good particle dispersibility.

[0140] Experiment Example 2

[0141] The cathode materials prepared in each embodiment and comparative example were used to make coin cells, and the electrochemical performance of the cathode materials prepared in each embodiment and comparative example was tested.

[0142] The prepared positive electrode material sample is processed into electrode sheets through a series of steps, and then the electrode sheets are assembled with other required components into a coin cell. The specific operation steps are as follows:

[0143] First, an 8 wt% PVDF binder needs to be prepared, using NMP as the solvent. Then, precisely weighed positive electrode material and acetylene black are mixed evenly using a planetary ball mill, with acetylene black serving as the conductive agent. Finally, the prepared PVDF solution is added to this mixture, and the mixture is thoroughly stirred again using a ball mill to form a homogeneous, viscous slurry. The positive electrode powder, acetylene black conductive agent, and PVDF binder are mixed in a mass ratio of 80:10:10.

[0144] The electrode slurry obtained above is uniformly coated onto one side of aluminum foil using a flatbed coating machine. Here, the aluminum foil serves as the current collector for the positive electrode material, and the coating thickness can be adjusted using the coating machine. The coated aluminum foil electrode sheet is then placed on a clean glass plate and dried in a vacuum heater. The dried positive electrode sheet is cut into circles (φ = 13 mm), and several blank aluminum foil circles of the same size are also cut. The mass of the blank aluminum foil is weighed and recorded. The cut electrode sheets are individually weighed and placed in the corresponding numbered positive electrode shells. Simultaneously, the separator is cut into circles with a diameter of φ = 19 mm. The negative electrode material is lithium metal (specification φ = 15.8 × 1.9 mm), and the battery shell is a CR2025 button cell with a diameter of 20 mm and a thickness of 2.5 mm. Finally, all are transferred to a glove box for battery assembly. Battery assembly is performed in an argon-filled glove box (water content ≤ 1 ppm, oxygen content ≤ 1 ppm).

[0145] The specific methods for electrical performance testing are as follows:

[0146] The chemical performance of the fabricated coin cells was tested using a LAND battery test cabinet. The current density during charge / discharge testing is expressed as the charge / discharge rate "C". The battery voltage range during charge / discharge was 3.0-4.3V (vs. Li / Li). + All electrochemical performance tests were conducted at room temperature (25°C).

[0147] The measured results are recorded in Table 1.

[0148] Table 1. Statistical analysis of the electrochemical performance of each embodiment and comparative example.

[0149]

[0150] As can be seen from Table 1, all embodiments of the present invention have good electrochemical performance.

[0151] Comparing Comparative Example 1 with Example 1, the cycle performance of Comparative Example 1 is significantly worse than that of Example 1, indicating that the electrochemical performance of the cathode made from the high-nickel-based precursor prepared by conventional preparation methods is worse than that of the cathode made from the precursor prepared in the examples of this application.

[0152] Comparing Comparative Example 2 with Example 1, Comparative Example 2 showed significantly worse discharge capacity, coulombic efficiency, and cycle performance compared to Example 1. This indicates that if the preparation method provided by the present invention is not followed in stages and repeated cycles, it will be impossible to obtain the precursor with good electrochemical performance provided by the present invention.

[0153] Comparing Comparative Example 3 with Example 1, the cycling performance of Comparative Example 3 was significantly worse than that of Example 1, indicating that if the pH is not controlled in the manner of the present invention, it will be impossible to obtain the precursor with good electrochemical performance provided by the present invention.

[0154] Comparing Comparative Example 4 with Comparative Example 5, the electrochemical performance of Comparative Example 4 was not improved compared to Comparative Example 5, indicating that the preparation method provided by the present invention is more suitable for preparing precursors of high nickel-based cathode materials.

[0155] In summary, the nickel-based single-crystal hydroxide precursor provided in this embodiment of the invention is a true single-crystal material with a regular morphology, good size, and good dispersibility. After sintering, the cathode material prepared with it does not require crushing or grading. The cathode material can inherit the crystal structure of the single-crystal precursor and has the characteristics of lithium storage structure with few or no defects. It has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0156] The preparation method provided by this invention develops a novel single-crystal precursor preparation technology with synergistic regulation of nucleation, ripening, and growth. By employing a stepped-feed nucleation technique, the agglomeration of amorphous nanocrystal nuclei is significantly reduced, resulting in the preparation of micro / nano-scale, highly dispersed, and pre-ripened nickel-based single-crystal hydroxide nuclei. Synergistic control of crystal growth enables the controllable preparation of highly dispersed, large single-crystal hydroxide precursors. The single-crystal precursor prepared by this method has a controllable D50 range of 1–5 μm, uniform particle size distribution, high dispersibility, and controllable crystal structure. The process is simple and requires no additional dispersant. This single-crystal precursor exhibits uniform morphology and good product consistency, allowing for large-scale production. Applying this method to the synthesis of single-crystal cathode materials enables the sintering preparation of true single-crystal high-nickel cathode materials under conditions of sintering temperature <800℃ and lithium overload ratio ≤5%, achieving energy conservation and emission reduction from the source, promoting a green and economical approach. The cathode material obtained from this precursor inherits the crystal structure characteristics of the single-crystal precursor, possesses lithium storage structure characteristics with few or no defects, and has advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0157] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-based single-crystal hydroxide precursor, characterized in that, include: Staged nucleation: Nucleation: A mixed metal salt solution, an alkaline solution, and ammonia water are introduced into the reaction vessel in a parallel flow. The pH of the reaction vessel is controlled at 12.5~13.0, and the ammonia concentration is maintained at 1.5~2.5 mol / L for 20~60 min. Maturation: Stop feeding the mixed metal salt solution, alkaline solution and ammonia water, and maintain for 20~60 minutes; The cyclic nucleation-ripening step is repeated 3 to 10 times to complete the hierarchical nucleation; Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia water to make the solution pH 10.5~11.5, maintain the ammonia concentration 1.5~2.5mol / L, and stop all feeding after 20~100h to reach the target particle size; The slurry should be aged for 0.5 to 2 hours. The entire reaction process takes place at a temperature of 60~90℃; The precursor has the chemical formula Ni 1-x-y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3; The precursor is a primary particle with a D50 of 1~5μm, a single crystal primary particle size range of 0.2~2μm, and a polyhedral morphology.

2. The preparation method according to claim 1, characterized in that, The polyhedron is a prism-shaped cubic polyhedron with a lateral aspect ratio of (1~5):1 and a specific surface area of ​​<10m². 2 / g.

3. The preparation method according to claim 1, characterized in that, Includes at least one of the following features (1) to (4): (1) The bottom liquid in the reactor accounts for 50-60% of the reactor volume, the ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0; (2) The concentration of metal ions in the mixed metal salt solution is 1~2 mol / L, and the injection flow rate of the mixed metal salt solution during nucleation is 10 mL / min~2 L / min; (3) After aging, the following steps are taken: the precipitate is extracted from the slurry, and washed sequentially with alkaline solution and deionized water at a temperature of 60~90℃ until the pH value of the precipitate is lower than 10, and then dried to obtain the precursor; (4) The concentration of the ammonia water is 10~14 mol / L; the alkaline solution is sodium hydroxide solution with a concentration of 8~10 mol / L.

4. The preparation method according to claim 1, characterized in that, The flow rate of ammonia solution is 5 mL / min to 1 L / min, and the flow rate of sodium hydroxide solution is 5 mL / min to 1 L / min.

5. A method for preparing a positive electrode material, characterized in that, The method includes mixing and sintering a lithium source with a precursor prepared by any one of claims 1 to 4, wherein the molar ratio of lithium in the lithium source to the metal in the precursor is 1:1.01 to 1.

05.

6. The preparation method according to claim 5, characterized in that, The sintering conditions are as follows: hold at 400~500℃ for 2~6 hours in an oxygen atmosphere, then raise the temperature to 680~750℃ and hold for 8~15 hours.

7. A positive electrode material, characterized in that, It is prepared by the preparation method described in claim 5 or 6.

8. A positive electrode, characterized in that, Including the cathode material as described in claim 7.

9. A battery, characterized in that, Includes the positive electrode as described in claim 8.

Citation Information

Patent Citations

  • Preparing method of large-granularity single-crystal lithium ion battery three-element positive electrode material

    CN109286016A

  • Method for preparing high-nickel ternary single crystal material precursor through coprecipitation method

    CN114436346A

  • A method for preparing single crystal high nickel positive electrode material

    CN115028210B

  • Methods for preparing nickel-cobalt-manganese ternary positive electrode material with large single crystal morphology and precursor thereof

    CN111943279A